Ring-opening polymerization of diepoxides as an alternative method to overcome PEG dilemma in gene delivery. (3rd January 2018) - Xiao, Ya-Ping; Zhang, Ji; Liu, Yan-Hong; Chen, Xiao-Chuan; Yu, Qing-Ying; Luan, Chao-Ran; Zhang, Ju-Hui; Wei, Xi; Yu, Xiao-Qi
Abstract: Gene therapy has shown great potential in the treatment of various diseases, and the development of low-toxic and efficient gene carriers is still one of the burning issues for gene therapy. PEGylation is generally regarded as an efficient strategy to improve the biocompatibility of non-viral vectors. However, PEGylation also led to several problems such as lower cellular uptake, difficult endosomal escape and much reduced transfection efficiency, which was described as "PEG dilemma". We herein devote to the development of polymeric gene vectors that can overcome such dilemma via diepoxide ring-opening polymerization (DEROP) of low molecular weight PEI, and unmodified PEI and PEG-grafted PEI were used for comparison. Transfection experiments with various concentrations of serum revealed that the DEROP polymers gave much higher transfection efficiency together with better serum tolerance than PEI and PEGylated ones. Protein adsorption and flow cytometry assays further proved their better serum resistance. Besides, confocal microscopy suggested that the polyplexes formed from these polymers could escape from endosome/lysosome more efficiently than those derived from PEGylated material. In vivo biochemical studies also reflect good biocompatibility of the DEROP polymers. Results demonstrate that such polymer construction strategy gave cationic materials with both high transfection efficiency and improved biocompatibility, and afforded an effective way to overcome PEG dilemma. Graphical abstract: Image 1 Highlights: DEROP polymerS were designed to overcome "PEG dilemma" in non-viral gene delivery. These polymers gave much higher transfection efficiency than PEI and PEGylated ones. These polymers showed good or better biocompatibility relative to PEGylated PEI. The DEROP strategy might be a promising method to construct efficient gene vectors.